2015
DOI: 10.1021/acscatal.5b00991
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom-Doped Graphene-Based Materials for Energy-Relevant Electrocatalytic Processes

Abstract: To address the aggravating energy and environment issues, the cheap, highly active, and durable electrocatalysts as noble metal substitutes both at the anode and cathode are actively pursued. Among them, heteroatom-doped graphene-based materials show extraordinary electrocatalytic performance, some even close to or outperforming the state-of-the-art noble metals such as Pt and IrO 2 -based materials. This review provides a concise appraisal on graphene doping methods, the possible doping configurations and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
549
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 856 publications
(557 citation statements)
references
References 270 publications
(752 reference statements)
4
549
0
4
Order By: Relevance
“…Graphene is such a kind of new carbon material. 135,136 However, there is still no ideal graphene commercially available. Many defects or impurities exist in the graphene from present fabrication methods.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Graphene is such a kind of new carbon material. 135,136 However, there is still no ideal graphene commercially available. Many defects or impurities exist in the graphene from present fabrication methods.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…However, in the future energy supply based on clean and renewable energy will dominate over the dependency on fossil fuels and this addresses challenges for technology development [1,2]. Water electrolysis is a promising method for storing intermittent electrical energy from renewable resources, such as sun and wind, in the form of hydrogen fuel [3].…”
Section: Introductionmentioning
confidence: 99%
“…Water electrolysis is a promising method for storing intermittent electrical energy from renewable resources, such as sun and wind, in the form of hydrogen fuel [3]. Electrochemical water splitting in alkaline media includes two half reactions: the hydrogen evolution reaction (HER, 4H 2 have shown high activity toward OER in acidic and alkaline media [4,5], and among the non-noble metal OER electrocatalysts, nickel (Ni) based electrocatalysts have shown very promising performance for OER in alkaline media [6][7][8][9][10]. For HER, Pt based materials are known as the most efficient HER catalysts in both acidic and alkaline media [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] During the past few years, transitional metal sulfides such as nanometer-scaled MoS 2 and WS 2 have attracted considerable attention in HER fields because of their low cost, high chemical stability, and excellent electrocatalytic properties. [8][9][10][11][12][13] Studies concluded that the unsaturated sulfur atoms on the edges of the 2D MoS 2 layers play a crucial role in HER catalysis 14 and the electric conductivity of catalysts is another crucial factor to affect the electrocatalytic activity.…”
mentioning
confidence: 99%